Имплементарный подход при моделировании энергетических процессов динамически позиционирующего судна - Будашко, В.В. (Електротехніка і електромеханіка, 2015)
В результате анализа энергетических процессов в судовых энергетических установках комбинированных пропульсивных
комплексов в различных эксплуатационных режимах создана стратегия построения математических моделей указанных комплексов. Стратегия основана на имплементации векторов возмущающих воздействий, изменяющих гидродинамические характеристики судна, на векторную плоскость энергетических характеристик. Предложенный подход к
моделированию энергетической установке судна, находящегося в режиме динамического позиционирования, позволил
учесть: а) особенности настроек ПИД-регуляторов частотных электроприводов подруливающих устройств; б) автоматических регуляторов напряжения среднеоборотных дизель-генераторов; в) эксплуатационные характеристики всех
управляемых объектов комплекса и судна при передаче мощности к гребным винтам. У результаті аналізу енергетичних процесів у суднових енергетичних установках комбінованих пропульсивних комплексів в різних експлуатаційних режимах створена стратегія побудови математичних моделей зазначених комплексів. Стратегія заснована на імплементації векторів збурюючих впливів, які змінюють гідродинамічні характеристики
судна на векторну площину енергетичних характеристик. Запропонований підхід до моделювання енергетичної установки судна, яке знаходиться у режимі динамічного позиціонування, дозволив врахувати: а) особливості налаштувань
ПІД-регуляторів частотних електроприводів підрулюючих пристроїв; б) автоматичних регуляторів напруги середньо-обертових дизель-генераторів; в) експлуатаційні характеристики всіх керованих об'єктів комплексу й судна при
передачі потужності до гребних гвинтів. Purpose. Creation of a mathematical model of the ship's power
plant (SPP) combined propulsion complexes (CPC) that takes
into account the behavior of all objects, including the ship itself,
the transfer of power from the medium speed diesel generators
on the propellers, which will allow to take into account the hydrodynamic properties of the vessel and their impact on the
energy processes in SPP CPC. Methodology. The analysis of
energy processes in the SPP CPC in different operating conditions resulted in creation of a strategy for constructing mathematical models of SPP CPC. This strategy is based on the implementation on the vector plane resulting power characteristics
of SPP vectors disturbances, leading to the deviation of the hydrodynamic characteristics of the ship during operation dynamic positioning. The result allowed to consider not only the
features of setting PID-governors of frequency converters of
electric thrusters but the automatic voltage regulators of medium speed diesel generators as well. Results. Within the research work a software package Ships_CPC in MatLab/Simulink was developed under the state budget project
«Concepts, technologies and ways of improving ship power
plants combined propulsion complexes» at the Department of
Electromechanics and Electrical Engineering of Odessa National Maritime Academy. Originality. This complex represents
a set of functional blocks of the components SPP CPC, built on
the principle of «input-output». The simulation results demonstrate the ability to use software package Ships_CPC to study
the effect of various settings on the energy regulators of processes SPP CPC, which can develop and integrate the different
strategies of automatic voltage regulators. Practical value.
Since software complex Ships_CPC was developed under Open
system technology, it can reorganize, re-tune and integrate in
processes of any difficulties with further completion in the form
of a universal structure.